﻿Taxonomy of the genus Peucobius Townes (Hymenoptera, Ichneumonidae, Sisyrostolinae) - Andrey I. Khalaim; Enrique Ruíz-Cancino; Juana Maria Coronado-Blanco (Journal of Hymenoptera Research, 2023)
The genus Peucobius Townes previously comprised two species occurring in the Nearctic region: P. fulvus Townes and P. piceus Townes. In the current study we revise this genus, transfer it to the subfamily Sisyrostolinae (comb. nov.), and describe two new species – P. bennetti Khalaim & Ruíz-Cancino, sp. nov. from Central Mexico and P. shimizui Khalaim, sp. nov. from Japan. The genus Lygurus Kasparyan occurring in Russian Far East and Taiwan is morphologically similar to Peucobius; characters for distinguishing these two genera are provided for the first time with the use of colour photographs. Identification keys to four world species of Peucobius, and to species of Lygurus and Peucobius occurring in the East Palaearctic region, are provided. We suggest that species of Peucobius are associated with xyelid sawflies (Xyelidae) whose larvae feed in staminate pine cones.